2014
DOI: 10.1590/0074-0276140126
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles species composition explains differences in Plasmodium transmission in La Guajira, northern Colombia

Abstract: Malaria in La Guajira, the most northern state of Colombia, shows two different epidemiological patterns. Malaria is endemic in the municipality of Dibulla whereas in Riohacha it is characterised by sporadic outbreaks. This study aimed to establish whether differences in transmission patterns could be attributed to different vector species. The most abundant adult female species were Anopheles aquasalis, exclusive to Riohacha, and Anopheles darlingi, restricted to Dibulla. Anopheles mosquitoes were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…neomaculipalpus [33], 98% for An. pseudopunctipennis [52] and 99% for An. albimanus , and 99% for An.…”
Section: Discussionmentioning
confidence: 99%
“…neomaculipalpus [33], 98% for An. pseudopunctipennis [52] and 99% for An. albimanus , and 99% for An.…”
Section: Discussionmentioning
confidence: 99%
“…Anopheles albimanus larvae were found in the three states, principally associated to larval habitats with standing water and the presence of vegetation. This species was associated with permanent larval habitats with turbid water in Córdoba, as in other parts of Latin America [ 24 , 30 – 42 ]. The results showed that An.…”
Section: Discussionmentioning
confidence: 99%
“…Localities (denoted by yellow dots) where the primary malaria vector Nyssorhynchus darlingi has been reported infected with Plasmodium vivax or Plasmodium falciparum incriminated by molecular methods during 2005 to 2017[8,35,59,60,73,80,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Map made in Google Earth Pro[83,84].…”
mentioning
confidence: 99%